O sujeito ativo do ICMS importação: interpretação do art. 11, I, "d", da lei complementar 87/96 de acordo com a constituição federal - Zotelli, Valeria (2008)
This study aims to the constitutional definition of the creditor of ICMS incident on transactions related to the circulation of goods, including imported commodities, as well as an analysis of the constitutionality of the terms of article 11, I, "d" of the Complementary Law 87/96. According to the literal disposition of the above mentioned article, the tax is due to the State in which the establishment of physical entry of the goods is located. Nevertheless, this determination represents an inconsistency with the complementary law which establishes as the event of levy the accomplishment of any operation involving mere legal circulation of goods. We have also searched for a systemic interpretation of the referred legal command, in light of the role assigned by the Federal Constitution to the complementary laws. Finally, we have also analyzed some decisions of Federal Supreme Court under the matter, in order to offer judicial solutions for the problem object of the present study